Screening of Exopolysaccharides and Polyhydroxyalkanoates producing bacteria isolated from SPUR of Estremadura - Catalão, Marta Alexandra Simões (2021)
Marine environments represent a huge biodiversity due to their several different habitats, being abundant in unknowns’ microorganisms and a source of new biomolecules, namely exopolysaccharides (EPS) and polyhydroxyalkanoates (PHA), with unique physical characteristics with application in pharmaceutical industry, medical, cosmetics, food and in bioplastic production. EPS are biopolymers excreted by bacteria when exposed to extreme conditions. In contrast, PHA are biodegradable bioplastics accumulated by bacteria as carbon stock and/or energy, in conditions with limited growth and carbon source in excess. The objective of this work was evaluating the capacity of bacteria isolated from marine sediments collected off the Estremadura SPUR, Portugal, to produce biopolymers. These sediments were collected from deep-sea, in depths between 230-400 meters. In total, 67 strains were isolated and tested in 30 mL cultures with promising results, where all bacteria showed capacity to produce EPS and PHA. In consideration of growth and productivity, some bacteria were tested in 200mL. According to these results, bacteria that showed the most promising results in relation to growth (> 0.80 g/L), EPS production (> 0.28 g/L) and PHA accumulation (fluorescence when coloured with Nile Blue dye) were studied in biorreator. The pH was controlled (7), temperature (30ºC), aeration (1vvm) and pO2 (20%) over the assay. The best results were obtained by SPUR-41 with a production of 1.83 g/L of EPS and a specific growth rate of 0.25 h-1 when cultivated in medium containing 20 g/L of glucose, 4 g/L of yeast extract and 2 g/L of peptone in bioreactor. The composition of biopolymers and taxonomic characterization of bacteria were performed to improve the characterization of the full production process.